'Relationships for Me are the Key for Everything': Early Childhood Teachers' Subjectivities as Relational Professionals. (September 2014) - Warren, Alison
Relational professionalism in early childhood teaching has been described as reflecting professional ethic of care values, as well as historical maternalist views. In Aotearoa/New Zealand, early childhood teachers negotiate conflicting contexts of professionalisation and maternalism. A strategic plan for early childhood education has emphasised teaching qualifications, and professional standards regulate early childhood teacher education and teacher registration. This article discusses findings from two participants involved in a post-structural study of newly qualified early childhood teachers' negotiations of their subjectivities within three dominant discourses. The authority discourse positioned the participants as claimed by the authority of qualifications and accountability requirements, while also claiming authority as knowledgeable and qualified. The identity work discourse positioned participants as responsible for shaping their own professional identities. A dominant discourse of relational professionalism positioned participants as relational professionals who engaged in warm, trusting and positive professional relationships. Data from two participants shows how they engaged in discursive practices in individual and complex ways in order to actively negotiate their subjectivities within the relational professionalism discourse.